Association of breed characteristics with milk production in Murrah buffaloes - Bharadwaj, A; Dixit, V B; Sethi, R K; Khanna, S (The Indian Journal of Animal Sciences, 2007)
The study was conducted to establish relationship between some breed characteristics of Murrah buffaloes such as horn pattern, head, face, colour of skin coat, tail switch, udder and teat conformation, skin thickness and temperament with milk production. Observation on 245 lactating buffaloes from institute and 150 from field were recorded. These buffaloes were grouped into different categories based on level of variation in the morphological characters of each animal. The data were statistically analysed and relationship of each character with milk yield was examined. The results indicated that coat colour, head and face, tail switch, shape of udder and teats and skin thickness were associated with milk production. The lactation milk yield produced by buffaloes having jet black colour was significantly higher (2195±34 kg) than buffaloes with dark tan colour (1863±30 kg). The lactation milk yield of buffaloes possessing flat head was significantly higher than buffaloes with bulging head (2069±25 vs 1686±98 kg). No difference in milk yield was observed between buffaloes having different shape of horn or face. Significantly higher milk yield was obtained in buffaloes having long and deep udders with higher rear attachment than those having short and shallow udders with low rear attachment. The milk yield was higher for cylindrical shaped (2204±28 kg) as compared to bottle (1927±43 kg) or funnel (1507±41 kg) shaped teats. Milk production of docile buffaloes was significantly higher (2120±27 kg) than those of nervous (1829±49 kg) and aggressive buffaloes (1743±147 kg). The milk yield was also significantly higher in buffaloes having thin skin (2184±38 kg) than medium (1973±35 kg) and thick skinned buffaloes (1848±47 kg).